2020
DOI: 10.1002/brb3.1742
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted therapy for upper‐limb rehabilitation in subacute stroke patients: A systematic review and meta‐analysis

Abstract: Background Stroke survivors often experience upper‐limb motor deficits and achieve limited motor recovery within six months after the onset of stroke. We aimed to systematically review the effects of robot‐assisted therapy (RT) in comparison to usual care on the functional and health outcomes of subacute stroke survivors. Methods Randomized controlled trials (RCTs) published between January 1, 2000 and December 31, 2019 were identified from six electronic databases. Poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 31 publications
1
69
0
Order By: Relevance
“…Although rehabilitation with neuro-rehabilitation robots has shown encouraging clinical results [ 5 18 ], it is currently limited to a very few hospitals and not widely used because of the associated high-cost and an infrastructural-requirement to station these large and complex devices with a high set-up time and limited usability [ 19 21 ]. Rehabilitation strategies need to take into account the multifaceted nature of the disability, which is self-changing (progressing or improving), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Although rehabilitation with neuro-rehabilitation robots has shown encouraging clinical results [ 5 18 ], it is currently limited to a very few hospitals and not widely used because of the associated high-cost and an infrastructural-requirement to station these large and complex devices with a high set-up time and limited usability [ 19 21 ]. Rehabilitation strategies need to take into account the multifaceted nature of the disability, which is self-changing (progressing or improving), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Another reports that chronic stroke hemiplegia patients receiving three months of robotic training had improvements in proprioceptive control, reactive balance, and posture control [ 22 ]. However, a systematic review and meta-analysis found that although RT has the benefit of low labor cost, when the same amount of RT is employed as conventional treatment, RT alone is not better than conventional treatment [ 23 ]. Is there a bias in efficiency studies because of one type of robot?…”
Section: Artificial Intelligence (Ai)mentioning
confidence: 99%
“…Robotic therapy adjunct to standard-intensity conventional therapy was more beneficial than standard intensity conventional therapy alone (Bertani et al, 2017;Veerbeek et al, 2017;Ferreira et al, 2018;Mehrholz et al, 2018). However, the meta-analysis also suggested that under similar training intensity, the improvement of upper limb function was comparable between robotic therapy and conventional therapy for stroke survivors (Veerbeek et al, 2017;Ferreira et al, 2018;Chien et al, 2020). It should be noted that those meta-analysis results derived in the aggregate of the general stroke population may not provide the best evidence of practice for stroke survivors with different levels of impairments (Winstein et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Despite increasing literature were presented, the effectiveness of robotics for rehabilitation in upper limb motor poststroke rehabilitation remains inconclusive (Bertani et al, 2017 ; Veerbeek et al, 2017 ; Ferreira et al, 2018 ; Mehrholz et al, 2018 ; Chien et al, 2020 ). Robotic therapy adjunct to standard-intensity conventional therapy was more beneficial than standard intensity conventional therapy alone (Bertani et al, 2017 ; Veerbeek et al, 2017 ; Ferreira et al, 2018 ; Mehrholz et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%